Distributive Justice and Structural Empowerment and Their Effects on Affective Commitment: The Mediating Role of Psychological Empowerment Among Employees of the Cirebon City Fire and Rescue Department - Asep Dwi Agustio; Sandi Nasrudin Wibowo (Majapahit Journal of Islamic Finance and Management, 2026)
This study examine the effect of Distributive Justice and Structural Empowerment on Affective Commitment, with Psychological Empowerment as a mediating variable among employees of the Fire and Rescue Service (DPKP) of the Cirebon City, Indonesia. A quantitative casual-associative approach was employed, utilizing Structural Equation Modeling – Partial Least Square (SEM-PLS). The population consisted of 240 Employees, and 150 respondents were selected via simple random sampling using the Slovin formula. Data were collected through a closed-ended Likert scale questionnaire (1-5) and analyzed using SmartPLS 4.0. The Results indicate that: (1) Distributive Justice positively and significantly afffects Affective Commitment; (2) Structural Empowerment positively and significantly affects Affective Commitment; (3) Distributive Justice positively and significantly affects Psychological Empowerment; (4) Structural Empowerment positively and significantly affects Psychological Empowerment; (5) Psychological Empowerment positively and signicantly affects Affective Commitment; (6) Psychological Empowerment significantly mediates the effect of Distributive Justice on Affective Commitment; however, (7) the mediation of Psychological Empowerment on the relationship between Structural Empowerment and Affective Commitment is not significant. These findings reinforce the relevance of Social Exchange Theory and provide practical implications for human resource management strategies in public sector organizations.